PERAN KOMUNIKASI ORGANISASI UNTUK MENINGKATKAN LOYALITAS KARYAWAN ADHI JAYA HOTEL KUTA – BALI - Mas Pradnyadewi, I Gusti Agung Ayu Putu; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2019)
ABSTRACT Communication has an important role in life, so also in organizations. The right organizational communication can facilitate management and employees to coordinate with each other. one of the results expected by the company is loyal employees The purpose of this study is to determine the extent to which organizational communication plays a role in increasing employee loyalty to Adhi Jaya Hotel Kuta. This study uses a qualitative descriptive method in the positivist paradigm. The results of this study indicate that family communication in the organization applied in Adhi Jaya Hotel Kuta plays an effective role in increasing employee loyalty. Organizational communication that is run in a family manner can provide openness, a sense of comfort when working and still respect each other between superiors and subordinates as well as fellow colleagues who are equal This is a factor in increasing employee loyalty to the company. Keywords : Communication Organization, Employees, Loyalty